Using SPSS for poverty and nutrition policy analysis - Quabili, Wahid (International Food Policy Research Institute, 2008)
Poverty and malnutrition in Nigeria is widespread and severe, and therefore, continues to be central to the development discourse. Sixty-four percent of rural Nigerians has a consumption level below the basic-needs poverty line, while forty-three percent of rural children, who are under five years of age, is stunted in growth. Thus, many rural Nigerians live under conditions of extreme vulnerability, both economically and physically, with limited abilities to cope with shocks that arise and safeguard their current level of well-being